2008
DOI: 10.1080/01421590701784349
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based teaching is as good as face to face lecture-based teaching of evidence based medicine: a randomized controlled trial

Abstract: Computer based teaching and typical lecture sessions have similar educational gains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 18 publications
5
121
0
4
Order By: Relevance
“…Our trial merits consideration as we undertook a randomized design to provide scientifically sound results. One of the strengths of the trial was that we were able to recruit more participants than previous trials [10][11][12] and this increases the precision of our findings. Furthermore, a cluster randomized trial design was chosen to reduce the effect of contamination.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Our trial merits consideration as we undertook a randomized design to provide scientifically sound results. One of the strengths of the trial was that we were able to recruit more participants than previous trials [10][11][12] and this increases the precision of our findings. Furthermore, a cluster randomized trial design was chosen to reduce the effect of contamination.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…With regards to EBM, there is no shortage of data that demonstrates that training courses can improve literature searching, critical appraisals, (Davis, Crabb, Rogers, Zamora, & Khan, 2008;Harewood & Hendrick, 2010;Thangaratinam et al, 2009) or even change clinical practice. (Straus, Ball, Balcombe, Sheldon, & McAlister, 2005) However, a recent systematic review of EBM "teach the teacher" courses concluded that there were no specific assessment tools for evaluating effectiveness of these courses, making it impossible to ascertain if they are having the desired effect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32]. Finally, multiple studies demonstrated that knowledge was equivalent (or better) between students learning through online lectures compared to traditional learning modalities, such as live didactic lectures [8,9,12,19,22,23,25,28,[33][34][35][36][37][38], with the exception of one study that found superior student knowledge acquisition from live lectures [39].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%